Desenvolvimento sintático em produções escritas de crianças de 1.º ciclo - Lobo, Maria; Batalha, Joana; Estrela, Antónia; Bragança, Bruna (Revista da Associação Portuguesa de Linguística, 2022)
This article presents a study on the syntactic development of children attending the 1st cycle of basic education based on their writing. We seek to (i) identify which are the predominant clause articulation processes at an early stage of compositional writing from the connectors that emerge at this stage; (ii) determine if the clause articulation processes evidence syntactic knowledge about the coordination and subordination processes; and (iii) determine the progression in the use of connectors over the course of a school year in this initial phase of compositional writing. We analyzed a corpus with 156 narrative texts written by students at grade 2, and a second corpus with 126 texts of the same students at grade 3. Results show us that connectives used in coordinate structures are predominant in children’s writing, although we can identify different profiles of syntactic development. A comparison between the texts of grade 2 and grade 3 shows an increase both in terms of the quantity and the diversity of the connectives used. Subordination becomes a more consistently used process of clause articulation in the narrative texts analyzed, with some connectives becoming more frequent and others emerging in students’ writing.